2020
DOI: 10.4142/jvs.2020.21.e50
|View full text |Cite
|
Sign up to set email alerts
|

Porcine parvovirus nonstructural protein NS1 activates NF-κB and it involves TLR2 signaling pathway

Abstract: Background: Porcine parvovirus (PPV) is a single-stranded DNA virus that causes porcine reproductive failure. It is of critical importance to study PPV pathogenesis for the prevention and control of the disease. NS1, a PPV non-structural protein, is participated in viral DNA replication, transcriptional regulation, and cytotoxicity. Our previous research showed that PPV can activate nuclear factor kappa B (NF-κB) signaling pathway and then up-regulate the expression of interleukin (IL)-6. Objectives: Herein, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The classical activation pathway is activated by most proinflammatory factors, such as TNF, interleukin 1 (IL-1), or viral and bacterial products. Several viral infections, including porcine parvovirus (PPV), herpes simplex virus (HSV) and measles virus (MV), were reported to activate NF-kappa B signaling pathway ( 40 42 ). Epstein-barr virus (EBV) could activate NF-kappa B signaling pathway and inhibit viral replication ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…The classical activation pathway is activated by most proinflammatory factors, such as TNF, interleukin 1 (IL-1), or viral and bacterial products. Several viral infections, including porcine parvovirus (PPV), herpes simplex virus (HSV) and measles virus (MV), were reported to activate NF-kappa B signaling pathway ( 40 42 ). Epstein-barr virus (EBV) could activate NF-kappa B signaling pathway and inhibit viral replication ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…TLR2 pathogen-associated molecular pattern (PAMP) recognition and signaling have also been shown to involve co-receptors such as CD14, and CD36 ( Figure 1 ) [ 9 ]. Because of TLR2’s ability to heterodimerize with several other TLRs, the list of PAMPs suggested to associate with TLR2 are substantial, including proteins from Epstein–Barr virus (EBV) [ 10 , 11 ], cytomegalovirus (CMV) [ 12 , 13 , 14 ], respiratory syncytial virus (RSV) [ 15 ], measles [ 16 ], hepatitis C virus (HCV) [ 17 , 18 , 19 , 20 , 21 , 22 ], herpes simplex virus -1 and -2 (HSV) [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], coronaviruses [ 39 , 40 , 41 , 42 ], parvovirus [ 43 , 44 ], and norovirus [ 45 ].…”
Section: Surface Toll-like Receptor Signaling: Initiationmentioning
confidence: 99%
“…PPV is a non-enveloped, single-stranded DNA virus in the Parvoviridae family and encodes two non-structural proteins, NS1 and NS2, and two structural proteins, VP1 and VP2 [ 99 ]. While little research has been done to investigate how PPV activates a surface TLR, there have been two studies demonstrating that the recognition of PPV by TLR2 may benefit the virus [ 43 , 44 ]. Jin et al demonstrated that PPV NS1 expressed by the pEGFP-N1-NS1 plasmid in HEK-293 cells induced the expression and production of TNF and IL-6 and that NS1-NF-κB signaling activation was mediated by TLR2 [ 43 ].…”
Section: Surface Tlr Associated Virus Interactionsmentioning
confidence: 99%
See 2 more Smart Citations